The Actualization of Qadiriyah-Naqshbandiyah Sufi Order Values in Modern Social Life - Mohamad Hudaeri; Istiqomah Istiqomah; Siti Nuriaulpah (Penerbit Hellow Pustaka, 2026)
Modernity, along with its social, economic, and technological changes, has brought about significant transformations in people's lifestyles, including in the spiritual and social dimensions. This phenomenon often fosters tendencies toward individualism and materialism, and erodes existing social relationships. In this situation, the Sufi order, as part of the Islamic Sufi heritage, plays a crucial role in maintaining the balance between the spiritual and social aspects of human life. This article aims to analyze how the values of the Qadariyah Naqsabandiyah (TQN) Order are implemented in social interactions in modern society. This research employs a qualitative approach through a literature review method that focuses on classical Sufi literature as well as more recent academic studies. The findings of the study indicate that the core values of TQN, such as dhikr (remembrance of God), sincerity, simplicity, spiritual discipline, and social solidarity, not only serve as tools for purifying the soul but also play a role in creating social piety, strengthening community cohesion, and developing social ethics amidst the challenges of the modern era. Thus, the Qadariyah Naqsabandiyah Order remains relevant as an Islamic spiritual model that is able to adapt to changing times.